2018
DOI: 10.1177/0021886318801277
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Power Struggles: A Multilevel Perspective on Incongruences at the Interface of Practice, Knowledge, and Identity in Radical Organizational Change

Abstract: Previous approaches to describing challenges inherent in radical organizational change have mainly focused on power struggles. A complementary but less researched view proposes that many problems occur because radical change causes certain incongruences within an organization. In line with the latter perspective, this article suggests that radical change leads to incongruences between "what they do" (practice), "what they know" (knowledge), and "who they are" (identity) as an organization; to achieve the chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
0
9
0
1
Order By: Relevance
“…Sensemaking about the undesirable consequences of a changed environment creates perception of loss. Previous studies have discussed perception of loss in the context of organizational change where there were unfavorable implications for workload, identity, job control, autonomy, status, power and relative benefits and costs (Bartunek et al , 2006; Chaudhry and Song, 2014; Hakak, 2015; Kump, 2019; Langley et al , 2012; Oreg et al , 2011; Robinson and Griffiths, 2005; Weber and Manning, 2001).…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…Sensemaking about the undesirable consequences of a changed environment creates perception of loss. Previous studies have discussed perception of loss in the context of organizational change where there were unfavorable implications for workload, identity, job control, autonomy, status, power and relative benefits and costs (Bartunek et al , 2006; Chaudhry and Song, 2014; Hakak, 2015; Kump, 2019; Langley et al , 2012; Oreg et al , 2011; Robinson and Griffiths, 2005; Weber and Manning, 2001).…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…Prior research supports a theory that voluntary employee turnover is problematic within the service industry when leaders fail to implement human capital strategies. Other findings suggested that leaders' lack of business direction supported a 68% failure rate in implementing workplace solutions [15]. The study's significance revealed workplace solutions for service industries, supported enhancements in employee motivation, succession planning, and profitability.…”
Section: ░5 Conclusionmentioning
confidence: 84%
“…Organizational change is modifying existing work routines and strategies that affect the whole organization [14]. Kump [15], emphasized that 68% of all organizational change strategies fail to deliver expected results or meet specific objectives. The failure of a strategic direction by automotive manufacturing senior leaders may define employees' resistance to support a strategy and adopt necessary behaviors that accomplish the organization's strategic mission [16].…”
Section: ░ 2 Literature Review 21 Organizational Changementioning
confidence: 99%
“…When the changes required conflict with the predominant organizational culture, these changes are less likely to be adopted (Howard‐Grenville et al, 2003) and the transition is made more difficult (Harris & Crane, 2002; Hengst et al, 2020). Similarly, changes in practices may be challenging because they can lead to intraorganizational conflicts of “who we are” as an organization (Kump, 2019). For example, farmers were found to be reluctant to change if the suggested measures were at odds with their knowledge and attitudes, that is, with how they thought that farming should be conducted (White & Selfa, 2013).…”
Section: An Environmental Belief Modelmentioning
confidence: 99%